COVID-19 and pregnancy. Review and update - Vigil De Gracia, Paulino (2020)
Objective: To search for all the information and available evidence on infection with SARS-CoV-2, a virus that appeared during the first 4 months of 2020, and pregnancy. Methods: Systematic review in PubMed and Google Scholar databases until April 25, 2020. We searched for published articles related to pregnant women infected with SARS-CoV-2. There was no language restriction. The search was extended to the references of the articles found. Results: In pregnant women with COVID-19, more than 90% of patients evolve mildly, 2% require intensive care. One maternal death has been reported. Prematurity occurs in approximately 25% of the cases, with predominance of late preterm infants; premature rupture of membranes presents in about 9%. Perinatal mortality is lower or similar to that of the general population, and vertical transmission has not been shown. Conclusions: Obstetrician-gynecologists must prepare to attend more cases with COVID-19 and therefore they need to know this disease. COVID-19 progresses similarly in pregnant and non-pregnant women, although it is associated to prematurity. While vertical transmission has not been demonstrated, horizontal transmission during vaginal birth is very likely.